THE IMPACT OF MANAGEMENT INFORMATION SYSTEM ON ORGANIZATIONAL PERFORMANCE WITH THE COMPOSITION OF TOP MANAGEMENT AS THE MODERATING VARIABLE - Purnamasari, Dian Indri; Hindria, Ratna (Research In Management and Accounting (RIMA), 2018)
The present research aims to study the impact of management information system on the performance of organization with the composition of top management as the moderating variable. The research objects are heads of university management, both state and private. The hypothesis testing was performed using Moderated Regression Analysis. The test results showed that the management information system positively affects the universities’ organizational performance. This means that the better the management information system, the higher the performance of a university. The composition of top management has no effect as the moderating variable between MIS and university performance. Thus, the composition of the top management does not reinforce the influence of management information system on the performance of organizations (universities).